Multinucleon Transfer Mechanisms in peripheral collisions of 40Ar + 64Ni at 15 MeV/nucleon. - Gkatzogias, Konstantinos; Souliotis, Georgios; Giannitsa, Chrysi; Koulouris, Stergios; Veselsky, Martin; Yennello, Sherry; Bonasera, Aldo (HNPS Advances in Nuclear Physics, 2026)
We report a systematic study of ejectiles from the interaction of a 15 MeV/nucleon 40Ar beam with a 64Ni target. The experimental data were obtained with the MARS spectrometer at the Cyclotron Institute of Texas A&M University in previous work of our group. Theoretical calculations were performed with the Deep-Inelastic Transfer (DIT) and the Constrained Molecular Dynamics (CoMD) models, both coupled to the statistical decay code GEMINI. The resulting mass, angular and momentum distributions have been compared with the corresponding experimental distributions. Both models describe the general trends of the data in a satisfactory way. We plan to further explore the role of specific model parameters (nuclear potentials in DIT, nuclear compressibilities in CoMD) to provide further insight into the mechanisms of nuclear reactions below the Fermi energy (10–35 MeV/nucleon).